Nanopore versus Illumina to study the gut bacterial diversity of sows and piglets between farms with high and low health status - Carla Tort-Miró; Laura Lorenzo-Rebenaque; Laura Montoro-Dasi; Santiago Vega; Juan Carlos Rodríguez; María-Paz Ventero; Maria Teresa Pérez-Gracia; Judith Guitart-Matas; Noemí Giler-Baquerizo; Ana Marco-Fuertes; Giuseppe D’Auria; Clara Marin; et al. (BMC Veterinary Research)
Abstract Background Antibiotics are used in animal husbandry to control infectious diseases. Different stressors can compromise animal health, leaving piglets vulnerable to pathogens, especially enterotoxigenic Escherichia coli (ETEC), which causes post-weaning diarrhoea (PWD), the major source of mortality and morbidity in swine production. Furthermore, PWD is a recurrent disease for certain farms, suggesting a link between gut microbial composition and animal health. The aim of this study was to identify the intestinal microbiota of pigs on farms with high health status (HHS) and low health status (LHS) to determine the relationships between sanitary status and gut health. Therefore, three pig farms with LHS presenting recurrent problems of PWD and three farms with HHS were selected to characterise the intestinal microbiome of sows and their piglets. 16 S rRNA gene sequencing technology was used to determine the associations of the gut microbiome with health. With the aim of bringing the MinION Nanopore device to the field for its portability and taxonomic resolution, the results obtained with Illumina were compared to those obtained with Nanopore. Results Overall, the results indicated remarkable differences in intestinal microbial communities between animals from LHS farms and those from HHS farms, suggesting that the microbiomes of LHS animals were enriched with potential pathogenic microorganisms, mainly from the Pseudomonadota phylum, such as the genus Escherichia-Shigella, and their associated related species. Moreover, animals from HHS were enriched with beneficial microorganisms, such as Lactobacillus spp., Christensenellaceae R7 group, Treponema, Acetitomaculum and Oscillospiraceae UCG-005. Conclusions This study identifies potential microorganisms that may contribute to health and disease in pig farms with HHS and LHS, suggesting that tracking their occurrence might provide insight into sanitary conditions. Moreover, this research highlights the compatibility between Illumina and Nanopore sequencing platforms, justifying the use of MinION Nanopore device in field applications for in situ studies of PWD. This application has the potential to enhance sustainable economic growth in swine farms by enabling more effective monitoring and management of animal health.